The analysis of the technico-economic indicators for the main crops in the S-W Region between 2009-2017 - Petruța Turek-Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The agriculture has represented an important source of food for mankind since the ancient times. Romania is a country that has fertile soils and a climate that offers favorable conditions for agriculture. These conditions can also be found in the Oltenia S-W Region where the agriculture represents an important resource having over a million hectares that are used for grain crops and for the oleaginous plants. Within this study we are going to analyze the indicators regarding the evolution of the cultivated surfaces, the productions and the prices of the main crops (wheat, corn, sunflower): the average, the annual growth rate, the deviations in absolute scales.
Keywords: Q10; Q11; 330; productions; prices; annual rate; variation parameter